Hypoxia Precondition Enhance the Therapeutic Effects of Mesenchymal Stem Cells via regulating TGF-β1 and IL-10 serial expression in Skin Excision Rat Models - Kustyah, Azizah Retno; Fatimah, Nandiah; Rizkiyani, Elytia Mutia; Ramadhanti, Olifiarsy Wiet; Istiqomah, Dyah Ayu Fitri; Hidayah, Nurul; Bhirau Wilaksono (International Journal of Cell and Biomedical Science, 2022)
Background: The skin excisional wound healing process involves an intricate-regulated series of cellular responses to reverse the formation of skin tissue integrity. This process requires paracrine communication involving anti-inflammatory cytokines and growth factors, especially interleukin 10 (IL-10) and TGF-β. On the other hand, hypoxic preconditioned mesenchymal stem cells (Hypoxia-MSCs) have been acknowledged to enrich IL-10 and TGF- β secretion contributing to accelerated wound healing compared to normal preconditioned mesenchymal stem cells (Normoxia-MSCs). Objective: This study aimed to compare Hypoxia-MSCs and Normoxia-MSCs in integrating the serial expression of IL-10 and TGF-β associated with improved collagen density in animal models of excision wounds. Methods: Thirty-six male Wistar rats with excision wounds were made as animal models using the 6 mm biopsy method. The rats were randomly divided into four groups consisting of four treatment groups: N-MSCs 1x106, H-MSCs 1x106, Control (PBS treatment), and Sham (untreated or healthy mice). The treatments were administered 2 times intraperitoneally on day 0. Skin tissue was collected on days 12, 18, and 24 post-injections. IL-10 dan TGF-β expressions were examined by qPCR. Results: This study showed that there was a significant increase in IL-10 and TGF-β after Hypoxia-MSCs and Normoxia-MSCs treatment compared to the Control group. Conclusion: Hypoxia-MSCs can improve the serial expression of IL-10 which leads to wound repair of the mouse model of excision wound. These results suggest that a hypoxic environment can enhance the therapeutic effect of MSCs.